EFEKTIVITAS MEDIA VIDEO TUTORIAL RECORDER TERHADAP KETERAMPILAN BERMAIN RECORDER SISWA KELAS VI SDN WRINGINANOM 2 GRESIK - MEGA HARUMAWATI, DESSY; YERMIANDHOKO, YOYOK (PGSD FIP UNESA, 2018)
The learning process is a process that will lead the students to understand something. Therefore it is needed media that can provide a holistic and effective understanding in the learning process. The learning media that can be used in this case is a video tutorial on how to play the soprano recorder. This study aims to determine whether or not and how the description of the effectiveness of video tutorial recorder media to the skills of playing recorders of grade VI students SDN Wringinanom 2 Gresik. This research uses experimental research concept with pretest-posttest control group design. The sample of this research is the grade 6 students of SDN 2 Wringinanom Gresik which totals 45 students. Stages in this study include giving pretest, followed by treatment and closed with posttest. Validity of instruments used in this study is (expert judgment) that is by consulting the instrument to the experts. The result of this study is that there is a significant effectiveness in the experimental class because the application of video tutorial recorder media in the learning process than control class without similar media is proved by T count> T table (11,323> 2,080). Keywords: recorder, effectiveness, and video.